THE CULTURE OF WRITTEN SPEECH FORMATION AT THE LESSONS OF UKRAINIAN ON THE BASIS OF COLLEGE - Khoma Tаtуana V. (Educological discourse, 2016)
The article deals with the urgent issue of the students’ speech development. The interconnection between the written and oral forms of speech is mentioned. Exercises and tasks on the culture of written speech formation are collected. The author offers different kinds of traditional and non-traditional dictations and provides the methodology of how to conduct them. The texts are taken from belles-lettres, history, arts, social and cultural contexts. They are professionally-orientedand are characterized on several levels: phonetics and phonemic, lexico-semantic, orthoepic, morphologic and syntactic. The attention is focused on the interconnection between the level of a person’s speech competence and the ability to feel confident in different communication situations.